A randomized clinical study using optical coherence tomography to evaluate the short‐term effects of high‐intensity interval training on cardiac allograft vasculopathy: a HITTS substudy. Issue 1 (13th December 2021) - Rafique, Muzammil; Solberg, Ole Geir; Gullestad, Lars; Bendz, Bjørn; Holm, Niels Ramsing; Neghabat, Omeed; Dijkstra, Jouke; Nytrøen, Kari; Rolid, Katrine; Lunde, Ketil
Abstract: Cardiac allograft vasculopathy (CAV) remains a leading cause of long‐term mortality after heart transplantation. Both preventive measures and treatment options are limited. This study aimed to evaluate the short‐term effects of high‐intensity interval training (HIT) on CAV in de novo heart transplant (HTx) recipients as assessed by optical coherence tomography (OCT). The study population was a subgroup of the 81‐patient HITTS study in which HTx recipients were randomized to HIT or moderate intensity continuous training (MICT) for nine consecutive months. OCT images from baseline and 12 months were compared to assess CAV progression. The primary endpoint was defined as the change in the mean intima area. Paired OCT data were available for 56 patients ( n  = 23 in the HIT group and n  = 33 in the MICT group). The intima area in the entire study population increased by 25% [from 1.8±1.4 mm 2 to 2.3±2.0 mm 2, P  < .05]. The change was twofold higher in the MICT group (.6±1.2 mm 2 ) than in the HIT group (.3±.6 mm 2 ). However, the treatment effect of HIT was not significant (treatment effect = –.3 mm 2, 95% CI [–.825 to .2 mm 2 ] P  = .29). These results suggest that early initiation of HIT compared with MICT does not attenuate CAV progression in de novo HTx recipients.